PMMA, Polyamide, and PEEK as Denture Bases: A Review of Physical, Mechanical, and Microbiological Properties - Sinha, Anamika; Panda, Sangram; Rath, Shakti; Garhnayak, Mirna (Journal of Nepalese Prosthodontic Society, 2025)
This review critically evaluates the physical, mechanical, and biological properties of commonly used denture base materials—polymethyl methacrylate (PMMA), polyamide, and polyether ether ketone (PEEK)—with emphasis on their clinical performance and biocompatibility. A systematic literature search was conducted using PubMed, Scopus, and Google Scholar for studies published between 2008 and 2024, focusing on in vitro, in vivo, and clinical investigations related to denture base materials, fabrication techniques, and microbial interactions. Advances in CAD/CAM and 3D printing technologies were assessed for their impact on prosthesis accuracy and durability. The review also highlights the role of material surface characteristics in microbial colonization, particularly Candida albicans, and the subsequent risk of denture stomatitis. Additional factors such as thermocycling, oral hygiene, and patient-related variables were considered for their influence on prosthetic longevity. This comprehensive analysis aims to inform evidence-based material selection and design strategies to improve functional and biological outcomes in removable prosthodontics.